2019
DOI: 10.1515/zsr-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting patterns in EU regulatory social policy: (still) supporting the market or social goals in their own right?

Abstract: Despite the fact that economic concerns are the main driver of the EU integration process, integration does carry a substantial social dimension. Yet, it remains an open question whether this social dimension ‘only’ supports the market or whether goals such as social justice, solidarity and employment conditions are independent of or even work against goals of market efficiency. To address this question the paper presents an original dataset on all 346 binding EU social policy acts adopted since the Union’s fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…While the enforcement of the Minimum Wage Directive is far from certain and faces strong resistance from European export capital and various Northern and Eastern European member states, the Recovery and Resilience facility shows that the 'old idea' of macroeconomic conditionality is still alive and well in the pandemic (H€ opner, 2021). In addition, Hartlapp (2019) has shown that EU social and employment policy legislation is primarily market-supporting in character rather than pursuing genuine social objectives. One example is the pillar of social rights, which so far only had a non-binding, symbolic character and concentrates mainly on individual rights.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the enforcement of the Minimum Wage Directive is far from certain and faces strong resistance from European export capital and various Northern and Eastern European member states, the Recovery and Resilience facility shows that the 'old idea' of macroeconomic conditionality is still alive and well in the pandemic (H€ opner, 2021). In addition, Hartlapp (2019) has shown that EU social and employment policy legislation is primarily market-supporting in character rather than pursuing genuine social objectives. One example is the pillar of social rights, which so far only had a non-binding, symbolic character and concentrates mainly on individual rights.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the growing tendencies towards Europeanization since the early 2000s have led scholars to look at the new forms of governance designed to be used to govern labour policy in the EU (Hodson and Maher, 2001;Kohler-Koch, 1999). The steering mechanisms created -which, unlike in fiscal policy, were not binding in character -inspired political science to produce an almost unmanageable mass of academic literature on 'policy learning' and 'soft steering mechanisms' (Bu¨chs, 2007;Eberlein and Kerwer, 2004;Hartlapp, 2006). In this context, some even spoke of the necessary emergence of a European labour policy in response to the more complex governance requirements of the Single Market and Monetary Union (cf.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the observation of Hartlapp ( 2019 , p. 61) seems to be valid when she states that “EU social policy has substantially changed, strengthening its market-supporting dimension, while social policy in its own right has been weakened”. According to our analysis, it is hard to deny that “social Europe is now more strongly arranged to promote market competitiveness and recommodification of labor” (p. 1359) and that “social policy is a function for the common market” (van Gerven and Ossewaarde 2018 , p. 1357).…”
Section: European Challenges and Policy Directions: An Empirical Analysismentioning
confidence: 99%
“…regelt(vgl. hierzu etwa Kaufmann 1982;Hartlapp 2019). Hiervon lässt sich appellative Politik unterscheiden, mit der den politischen Steuerungsmodi »Geld« und »Gesetz« -mit Blick auf bedeutende Reden, feierliche Erklärungen und Appelle an die Bevölkerung -der Modus der »guten Worte« zur Seite gestellt wird.…”
unclassified